Revolutionary Conceptions : Women, Fertility, and Family Limitation in America, 1760-1820 - Klepp, Susan E. (Book collections on Project MUSE., 2009)
By examining the attitudes and behaviors surrounding the contentious issues of family, contraception, abortion, sexuality, beauty, and identity, Klepp demonstrates that many American women--rural and urban, free and enslaved--began to radically redefine motherhood during the Age of Revolution as they asserted, or attempted to assert, control over their bodies, their marriages, and their daughters' opportunities.